The biomechanical effect of root amputation and degree of furcation involvement on intracoronally splinted upper molar teeth – An in vitro study - Szabó Veronika T.; Szabó Balázs; Paczona Balázs; Mészáros Csongor; Braunitzer Gábor; Szabó Balázs P.; Garoushi Sufyan; Fráter Márk (Netherlands, 2022)
Objectives: The aim of this study was to evaluate the effect of the amount of periodontal support and the presence or absence of root amputation on the fracture resistance of intracoronally splinted maxillary molar teeth.
Materials and methods: 48 extracted human upper first molars and 48 s premolars were included in the study. All teeth underwent standard mesio-occluso-distal (MOD) (molars) and standard occluso-distal (OD) (premolars) cavity preparation. After the preparation, all molars were root canal treated, and 48 molar-premolar units were created by intracoronal splinting. The units were randomly divided into 4 groups (Groups A-D, 12 units per group): in Groups C and D, the disto-buccal (DB) roots of the molars were amputated, while in Groups A and B, no root amputation was performed. All units were embedded in methacrylate resin at different levels: in Groups A and C, at 4 mm apically from the cemento-enamel junction (CEJ), while in Groups B and D, at 6 mm apically from the CEJ, mimicking the different stages of furcation involvement. All units were submitted first to dynamic and then to static, load-to-fracture mechanical testing. Fracture resistance values were recorded fracture mode was analysed.
Results: During the load-to-facture test, Groups A and B (without root amputation) were characterized by significantly higher fracture resistance values compared to Groups C and D (with root amputation) (p < 0.05). Regarding fracture mode, irreparable fracture was more frequent in Group D (with root amputation and advanced furcation involvement) than in any other group (n = 8).
Conclusions: Root amputation has a negative effect on the fracture resistance of intracoronally splinted upper first molar-second premolar units with modeled furcation involvement.